Ausbildungsmotive und die Zeitaufteilung der Auszubildenden im Betrieb - Felix Wenzelmann (Journal for Labour Market Research, 2012)
– This paper analyzes training motives of firms and the allocation of productive tasks at the workplace using data from the cost-benefit-survey of the Federal Institute for Vocational Education and Training for the year 2007 (BIBB-CBS 2007). We distinguish between two training motives, the investment and the production motive of training. The identification of these motives is via the retention strategy of the firm, which can be: retaining all apprentices, retaining only a part of them or retaining only in exceptional cases. The time apprentices are available for the firm is divided up into three categories: times of unskilled productive tasks, times of skilled productive tasks and times of 'unproductive' tasks. It can be shown that in investment oriented firms the shares of unproductive tasks are higher than in firms following the production motive. Additionally we analyze which other factors influence the allocation of task in the training firm. Especially the general school competence the apprentices have achieved before starting the training has a positive influence on the share of skilled tasks.
Keywords: D22; J24; J31; 330; Auszubildende; betriebliche Berufsausbildung; Ausbildungsverhalten; Arbeitszeitverteilung; Ausbildungsabsolventen; Personaleinstellung; Arbeitsproduktivität; Ausbildungsbetrieb; Ausbildungskosten; Ausbildungsplanung; Kosten-Nutzen-Analyse; BIBB-Erhebung